2015
DOI: 10.1111/pai.12403
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 expressed in mast cells recruited into skin or bone marrow induces the development of pediatric mastocytosis

Abstract: The data suggest that mast cells, recruited in the skin and BM by CCL2/CCR, may induce the development of pediatric mastocytosis through reducing IL-10 due to upregulating TG2 activity via transcription factor nuclear factor-κB. Thus, TG2 may be used in diagnosis of pediatric mastocytosis, particularly SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…After washing the membranes with PBST, they were treated with primary Abs against actin, MMP13, TNF-α, IL-1β, COX-2, or P65 (Cell Signaling Technology, Bevery, MA, USA), or collagen type II (Santa Cruz, CA, USA) diluted with PBST (1:1000). Membranes were washed with PBST and treated with horseradish peroxidase (HRP)-conjugated goat anti-mouse or HRP-conjugated goat anti-rabbit IgG (diluted to 1:5000~1:10,000) (Bethyl Laboratories, Montgomery, TX, USA) in PBST for 1 h. After washing, the protein bands were visualized by Enhanced Chemi-Luminescence using a chemiluminometer (ECL; Amersham Biosciences, Piscataway, NJ, USA) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…After washing the membranes with PBST, they were treated with primary Abs against actin, MMP13, TNF-α, IL-1β, COX-2, or P65 (Cell Signaling Technology, Bevery, MA, USA), or collagen type II (Santa Cruz, CA, USA) diluted with PBST (1:1000). Membranes were washed with PBST and treated with horseradish peroxidase (HRP)-conjugated goat anti-mouse or HRP-conjugated goat anti-rabbit IgG (diluted to 1:5000~1:10,000) (Bethyl Laboratories, Montgomery, TX, USA) in PBST for 1 h. After washing, the protein bands were visualized by Enhanced Chemi-Luminescence using a chemiluminometer (ECL; Amersham Biosciences, Piscataway, NJ, USA) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…MC-derived OSM stimulates the growth of microvascular endothelial cells, osteoblasts, and fibroblasts [ 139 ]. Furthermore, it was shown that in children with mastocytosis, MCs may migrate to the skin and BM as a result of the upregulation of CCL2/chemokine receptor 2 (CCR2) and vascular cell adhesion molecule (VCAM-1), and they may induce the expression/activation of transglutaminase 2 (TG2) [ 144 ]. Importantly, TG2 is a cross-linking enzyme that promotes the expression of inflammatory cytokines, histamine, and LTC4 [ 144 ].…”
Section: Cutaneous Mastocytosismentioning
confidence: 99%
“…Furthermore, it was shown that in children with mastocytosis, MCs may migrate to the skin and BM as a result of the upregulation of CCL2/chemokine receptor 2 (CCR2) and vascular cell adhesion molecule (VCAM-1), and they may induce the expression/activation of transglutaminase 2 (TG2) [ 144 ]. Importantly, TG2 is a cross-linking enzyme that promotes the expression of inflammatory cytokines, histamine, and LTC4 [ 144 ]. An assessment of the precise role of all MC mediators in the pathogenesis of mastocytosis requires further studies.…”
Section: Cutaneous Mastocytosismentioning
confidence: 99%